2020
DOI: 10.1186/s43054-019-0013-7
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin as an adjuvant therapy in preterm infants with neonatal sepsis, randomized trial

Abstract: Background: Neonatal sepsis (NS) is a systemic uncontrolled inflammatory response to an infectious agent, resulting in oxidative stress. Melatonin antioxidant and free radical scavenger proved to be safe in neonates. We aimed to evaluate the efficacy and safety of melatonin as adjuvant therapy in NS. This was an interventional trial conducted on 40 preterm neonates with NS diagnosed on the basis of clinical and laboratory criteria. They were simply randomized to melatonin treated (MT) (n = 20) and conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Five trials (19%) were judged as with an overall high risk of bias, based on various subdomains ( Figure 2 ) [ 21 , 25 , 26 , 31 , 44 ]. Risk of bias assessment revealed some concerns for 13 trials (50%), as they were not preregistered in trial registries, and no predefined statistical analysis plan and/or study protocol was published for these studies, which precluded selective data reporting judgement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Five trials (19%) were judged as with an overall high risk of bias, based on various subdomains ( Figure 2 ) [ 21 , 25 , 26 , 31 , 44 ]. Risk of bias assessment revealed some concerns for 13 trials (50%), as they were not preregistered in trial registries, and no predefined statistical analysis plan and/or study protocol was published for these studies, which precluded selective data reporting judgement.…”
Section: Resultsmentioning
confidence: 99%
“…The effects of any hormone or growth factor as therapeutic supplement in preterm infants was assessed in two studies [ 25 , 26 ]. The first study, by El-Kabbany et al [ 25 ], was conducted in 40 preterm infants (GA < 36 weeks) with early or late-onset sepsis (based on clinical signs and laboratory indicators including Rodwell’s hematological score ≥3). Participants received a single dose of melatonin (20 mg) or placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Neonatal sepsis (NS) is a main source of neonatal dreariness and mortality and a significant general medical issue, particularly in creating nations and especially in pre-term babies [14].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its important role as an antioxidant, a recent study has illustrated the importance of melatonin in glucose regulation, improving sepsis-induced hyperglycemia in an animal model (180). Exogenous melatonin as adjunctive therapy for sepsis in preterm and term infants has been associated with improvements in laboratory and clinical outcomes, due to the leading role of oxidative stress in pathogenesis of preterm morbidity and sepsis (181)(182)(183)(184)(185)(186)(187). In support of its amelioration in sepsis, a recent clinical trial has demonstrated improved patient outcomes when melatonin was used as an adjunctive therapy in adult sepsis (188).…”
Section: Sickness Behavior and Melatonin Leptin And Ghrelinmentioning
confidence: 99%